More significant role for Jakim - Ariffin, Muhammad Irwan (Star Media Group Berhad, 2018)
RECENTLY, there was an outcry among the public when the new federal government announced that the Malaysian Islamic Development Department (Jakim) would be reviewed. Given that Jakim has been receiving a hefty share of the national budget, many have raised their concerns on its performance as well as given suggestions on its role in the new Malaysia.